1993
DOI: 10.1128/aac.37.5.1086
|View full text |Cite
|
Sign up to set email alerts
|

Efflux-mediated fluoroquinolone resistance in Staphylococcus aureus

Abstract: Transport processes are used by all organisms to obtain essential nutrients and to expel wastes and other potentially harmful substances from cells. Such processes are important means by which resistance to selected antimicrobial agents in bacteria is achieved. The recently described Staphylococcus aureus norA gene encodes a membrane-associated protein that mediates active efflux of fluoroquinolones from cells. SA-1199B is a fluoroquinolone-resistant strain of S. aureus from which we cloned an allele of norA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
357
2
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(377 citation statements)
references
References 34 publications
15
357
2
3
Order By: Relevance
“…This gene encodes a multidrug efflux protein (NorA) capable of transporting fluoroquinolones outside the bacteria. Studies have shown that a mutant of S.aureus with a knockout in the norA gene -coding for the MDR pump -has a substantially increased sensitivity to a large number of antimicrobials, including therapeutically significant compounds [36][37][38]. As inihibitors of the NorA efflux pump, reserpine, omeprazole, and lansprazole can improve fluoroquinolone activity against strains expressing different levels of NorA [16].…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a multidrug efflux protein (NorA) capable of transporting fluoroquinolones outside the bacteria. Studies have shown that a mutant of S.aureus with a knockout in the norA gene -coding for the MDR pump -has a substantially increased sensitivity to a large number of antimicrobials, including therapeutically significant compounds [36][37][38]. As inihibitors of the NorA efflux pump, reserpine, omeprazole, and lansprazole can improve fluoroquinolone activity against strains expressing different levels of NorA [16].…”
Section: Discussionmentioning
confidence: 99%
“…13) However, the norA mutations in the TP178 (T→C) and SA-1199B (T→A) mutants differ from the flqB mutation. 4,5) Further studies are necessary to elucidate the mechanism of increased norA expression in the TP178 and SA1199B mutants.…”
Section: Northern Blotting and Primer Extension Analysismentioning
confidence: 99%
“…Decreased susceptibility to cationic antiseptic agents, i.e. an increase in MIC, has been attributed mainly to the excretion of drugs into the extracellular space by proton motive forcedependent multidrug-transport systems (Grinius et al, 1992;Kaatz et al, 1993;. In S. aureus, qacA (Rouch et al, 1990), qacB (Paulsen et al, 1996), smr (Grinius et al, 1992) and norA (Neyfakh et al, 1993), which encode multidrug-transporter proteins, have been identified as antiseptic-resistance genes which confer resistance to cationic antiseptic agents including dyes such as acriflavine, acrinol and ethidium bromide, quaternary ammonium compounds (QACs) such as benzethonium chloride and benzalkonium chloride, and biguanides such as chlorhexidine digluconate (Littlejohn et al, 1992;.…”
Section: Introductionmentioning
confidence: 99%